Mengembangkan Kemampuan Siswa dalam Menjawab Soal Kata dengan Menggunakan Permainan Kartu di Kelas VII SMP Negeri 2 Dharma Caraka Gunungsitoli Selatan - Nursayani Maru'ao (INTELEKTIUM, 2022)
Question words are some words that have been familiar to learners. These words have been introduced to the students since they were in the first semester of junior high school. Based on the researcher’s observation, the students of SMP Negeri 2 Dharma Caraka Gunungsitoli Selatan have learnt question words but it seems that the students get difficulties applying question words. Some students think that English is a difficult lesson, and it is because the students can not involve in the learning process. Nowadays, in the teaching-learning process, the students are the center of learning. The students must be active and a teacher as an instructor, motivator and supervisor. It means that a teacher should realize first his role in the teaching-learning process. In conducting this research, the researcher used Classroom Action Research. The subject of this research is the seventh-grade students of SMP Negeri 2 Dharma Caraka Gunungsitoli Selatan that consists of 44 students. The procedure of action implementation was done in some cycles. The cycles consist of planning, action, observation and reflection. In cycle 1, the researcher finds out that the students have bad grammar, they cannot make a question using question word. They also lack of vocabularies, afraid to ask something they do not understand to the researcher, still not active in the game process, and ashamed to express their idea. In cycle 2, the students are more active. It can be seen through the learning process, some students giving questions on the cases they do not understand and they also answer their friend’s question. They look enthusiasm to follow the learning process. In cycle 3, the students get a good improvement, they brave to perform their idea, only a few students who still ashamed, however some students get difficulties in grammar. Question words are some words that have been familiar to learners. These words have been introduced to the students since they were in the first semester of junior high school. Based on the researcher’s observation, the students of SMP Negeri 2 Dharma Caraka Gunungsitoli Selatan have learnt question words but it seems that the students get difficulties applying question words. Some students think that English is a difficult lesson, and it is because the students can not involve in the learning process. Nowadays, in the teaching-learning process, the students are the center of learning. The students must be active and a teacher as an instructor, motivator and supervisor. It means that a teacher should realize first his role in the teaching-learning process. In conducting this research, the researcher used Classroom Action Research. The subject of this research is the seventh-grade students of SMP Negeri 2 Dharma Caraka Gunungsitoli Selatan that consists of 44 students. The procedure of action implementation was done in some cycles. The cycles consist of planning, action, observation and reflection. In cycle 1, the researcher finds out that the students have bad grammar, they cannot make a question using question word. They also lack of vocabularies, afraid to ask something they do not understand to the researcher, still not active in the game process, and ashamed to express their idea. In cycle 2, the students are more active. It can be seen through the learning process, some students giving questions on the cases they do not understand and they also answer their friend’s question. They look enthusiasm to follow the learning process. In cycle 3, the students get a good improvement, they brave to perform their idea, only a few students who still ashamed, however some students get difficulties in grammar. In conducting this research, the researcher used Classroom Action Research. The subject of this research is the seventh-grade students of SMP Negeri 2 Dharma Caraka Gunungsitoli Selatan that consists of 44 students. The procedure of action implementation was done in some cycles. The cycles consist of planning, action, observation and reflection. In cycle 1, the researcher finds out that the students have bad grammar, they cannot make a question using question word. They also lack of vocabularies, afraid to ask something they do not understand to the researcher, still not active in the game process, and ashamed to express their idea. In cycle 2, the students are more active. It can be seen through the learning process, some students giving questions on the cases they do not understand and they also answer their friend’s question. They look enthusiasm to follow the learning process. In cycle 3, the students get a good improvement, they brave to perform their idea, only a few students who still ashamed, however some students get difficulties in grammar.